Investigation of knife quality by using forging and flame hardening methods - Balkhaya, .; Anhar, M. P.; Suwarno, .; M. S. M., Sani (IOP Publishing, 2019)
The research was conducted to investigate the quality of knives the material and the forging process against wear resistance. The forged material is AISI 1050 steel, AISI 4340 steel, AISI L-6 steel, and JIS SUP 9 steel. The manufacturing of the knives ware done by heating the material to a temperature ranging from 900-950°C then forged repeatedly manually until the temperature drop in between 650-675°C. Heating and forging are carried out several cycles to form a knife. Hardening was done by heating the knives to reach austenite temperature by flame hardening method, then quenching using water cooling media. research of wear resistance was done on the sharp side by using an actuator tribometer pin-on-plate. The results showed that wear and tear were influenced by the material and the treatment. The flame hardening process can be reduced the wear rate, the wear rate found on AISI 1050 steel knives is 5.439 x 10−4 mm3/Nm after being forged, while the lowest wear rate was found on AISI L-6 steel knife which ware 2.44 x10−5 mm3/Nm after flame hardening. The flame hardening process can reduce the wear rate, highest wear rate found on AISI 1050 steel knives ware 5.439 x 10−4 mm3/Nm after being forged, while the lowest wear rate was found on AISI L-6 steel knife which is 2.44 x 10−5 mm3/Nm after flame hardening. Therefore, it can be conclude that traditional knife quality especially the wear resistance can be improved by optimizing the heat treatment schedule.